Mononuclear Nickel(II) Complexes with Schiff Base Ligands: Synthesis, Characterization, and Catalytic Activity in Norbornene Polymerization - Xu, Yi-Mei (Polymers (Basel), 2017)
The nickel(II) catalyst has manifested higher catalytic activity compared to that of other late transition metal catalysts for norbornene polymerization. Therefore, several structurally similar trans-nickel(II) compounds of N,O-chelate bidentate ligands were synthesized and characterized. Both the electronic effect and the steric hindrance influence polymerization. The molecular structures of 2, 4 and 5 were further confirmed by single-crystal X-ray diffraction.